Morfofisiologia de Graviola (Annona muricata L.), Cumaru (Dipteryx odorata (Albl.) Willd.) e Copaíba (Copaifera langsdorffii Desf.) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2011)
Changes in net productivity of Amazonian ecosystems associated with variations in rainfall and temperature can significantly alter the global cycle of carbon. The objective of this study was to evaluate morphophysiological aspects of the species Graviola (Annona muricata), Cumaru (Dipteryx odorata) and Copaiba (Copaifera langsdorffii) submitted to water stress and luminous. For analysis of growth of the species, the observed variables were TCA (Absolute Growth Rate) and TCR (Relative Growth Rate) in height and leaf area of seedlings subjected to light restriction (50% light) and full sun. The data of gas flow were collected in the leaf tissues of each species, distributed in four treatments that combine normal conditions and water stress and luminous. The variables measured were: photosynthesis, stomatal conductance, transpiration and leaf temperature, determined using an infrared gas analyzer (IRGA). Multivariate analysis jointly by the Hotelling test for comparison of TCA in height and leaf area and TCR in leaf area of young plants of Graviola, Cumaru and Copaiba under two light levels showed significant differences (p <0.0001 ) and TCR in height (p = 0.0382). However, the Hotelling test specific to each specie, showed that Graviola presented better growth rates in height and leaf area to 50% of light (p = 0.0039), the opposite was observed for Cumaru (p = 0.0166 ). For Copaiba, rates of height growth were better to 100% of light and leaf area to 50% of light (p = 0.0005). The Bartlett test showed similarity coefficient (phi = 68.01%) when the species were in full sun and dissimilarity (phi = 21.49%) the restriction of 50% light. Regression analysis did not show a single pattern of growth in two levels of shading, since the plants species have different strategies in their morphophysiological behavior when subjected to stress. The results of factor analysis showed significant differences (p = 0.0389) in the photosynthetic rates of the species when subjected to the interaction of water stress and luminous, but the differences were not observed for Gs, E and Tf. The analysis by the Tukey test showed significant differences (p <0.01 and p <0.05) for transpiratórias and photosynthetic rates, stomatal conductance and leaf temperature of the species in most of the different treatments. Regarding the multivariate analysis using the Hotelling test showed that there were differences (p <0.0001) between T1 and T4. Given the importance of species, greater attention is required about the same in future scenarios of intense climate change.
Keywords: Espécies vegetais; Comportamento fisiológico; Análise de crescimento; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS E MANEJOS DE ECOSSISTEMAS AMAZÔNICOS